Meckel's Diverticulum in Children-Parameters Predicting the Presence of Gastric Heterotopia - Slívová, Ivana; Vávrová, Zuzana; Tomášková, Hana; Okantey, Okaikor; Penka, Igor; Ihnát, Peter (World journal of surgery, 2018)
BACKGROUND: The presence of gastric ectopic mucosa in Meckel's diverticulum is associated with a higher risk of development of complications. The aim of the present study was to investigate which demographic/clinical parameters predict the presence of gastric heterotopia in Meckel's diverticulum. METHODS: This was a retrospective cohort study conducted in a single institution (University Hospital Ostrava, Czech republic). All children who underwent laparoscopic/open resection of Meckel's diverticulum within a 20-year study period were included in the study. RESULTS: In total, 88 pediatric patients underwent analysis. The mean age of the children was 4.6 ± 4.73 years; the male-female ratio was approximately 2:1. There were 50 (56.8%) patients with asymptomatic Meckel's diverticulum in our study group. Laparoscopic resection was performed in 24 (27.3%) patients; segmental bowel resection through laparotomy was performed in 13 (14.8%) patients. Gastric heterotopia was found in 39 (44.3%) patients; resection margins of all patients were clear of gastric heterotopia. No correlation was found between the presence of gastric heterotopia and the following parameters: age, gender, maternal age, prematurity, low birth weight, perinatal asphyxia, distance from Bauhin's valve and length of Meckel's diverticulum. The width of the diverticulum base was significantly higher in patients with gastric heterotopia (2.1 ± 0.57 vs. 1.2 ± 0.41 cm; p < 0.001). CONCLUSIONS: According to the study outcomes, the width of the diverticulum base seems to be a significant predictive factor associated with the presence of gastric heterotopia in Meckel's diverticulum. The laparoscopic/open resection of asymptomatic MD with a wide base should therefore be recommended.
Keywords: laparoskopie; Infant; Choristoma; předškolní dítě; retrospektivní studie; Gastric Mucosa; Humans; Cohort Studies; laparotomie; mužské pohlaví; Laparotomy; Laparoscopy; Child, Preschool; choristom; Adolescent; Meckelův divertikl; ženské pohlaví; lidé; mladiství; žaludeční sliznice; kohortové studie; dítě; Child; Meckel Diverticulum; Male; Retrospective Studies; kojenec; Female